Coping styles and symptomatic manifestation of first-episode psychosis: Focus on cognitive performance. (February 2019) - Stramecki, Filip; Kotowicz, Kamila; Piotrowski, Patryk; Beszłej, Jan Aleksander; Rymaszewska, Joanna; Samochowiec, Jerzy; Samochowiec, Agnieszka; Moustafa, Ahmed A.; Jabłoński, Marcin; Podwalski, Piotr; Waszczuk, Katarzyna; Wroński, Michał; et al.
Highlights: Patients with first-episode psychosis prefer maladaptive coping Maladaptive coping might be related to worse performance of visuospatial/constructional and language abilities in first-episode psychosis. Lower odds of using adaptive coping might be associated with depressive symptoms. Abstract: Cognitive deficits are widely observed in patients with psychosis and represent one of most important determinants of functional outcomes. It has been shown that patients with psychosis prefer maladaptive coping strategies over active coping styles. However, it remains unknown whether cognitive impairments are related to coping styles in psychotic disorders. Therefore, the aim of this study was to assess whether cognitive deficits observed in patients with first-episode psychosis (FEP) might impact the use of specific coping strategies. We recruited 40 FEP patients and 35 healthy controls. In our study, FEP patients were more likely to use maladaptive coping styles after adjustment for education level and medication effects. The use of maladaptive coping strategies was associated with greater impairments of visuospatial/constructional abilities and language skills in FEP patients. In addition, lower odds of using adaptive coping were related to higher levels of depressive symptoms in the group of patients. Adaptive coping was associated with better global cognitive performance in healthy controls. Our results indicate that cognitive impairments, especially worse performance of visuospatial/constructional abilities and language skills, might be related to the preference of maladaptive coping strategies. Lower odds of using adaptive coping styles might be associated with more severe depressive symptomatology.